THE PUNNAPRA – VAYALAR REVOLT AND THE FREEDOM MOVEMENT - N. Sasidharan
N. Sasidharan's "The Punnapra-Vayalar Revolt and the Freedom Movement" is a comprehensive article about the events that lead to the famous Punnapra-Vayalar Revolt. He quotes extensively from the official records, and declares that the Revolt "was the outcome of the general strike of 1938". It places the general strike, the Revolt and the leaders of the time in an unusual perspective, and depicts this illustrious chapter in the history of Kerala as a sort of well-scripted drama that deserves closer scrutiny.